The art of collaborating with AI : harnessing the power of diverse thinking - Smith, D. V. L.; Riley, Adam (Marketing strategist) (Routledge, 2025)
"We are at a momentous inflection point in our evolutionary history: generative AI is becoming mainstream, transforming the world of work, and specifically that of knowledge workers. This book helps you to navigate your upskilling journey to remain relevant and to add value in the workplace. Knowledge workers must face up to the fact that there is a need to urgently reboot their skillset to survive and thrive in the new AI era. Many of the historic competences and points of differentiation that employees could offer are being challenged with AI technology. This book is all about building the power skills that knowledge workers will need to develop in order to maintain a competitive edge and work effectively alongside AI. It's a future where AI will now do a lot of the heavy lifting, and one in which employers will increasingly be looking for people to add value in areas where AI is weak. In particular, this puts the spotlight on the need for workers to dial up their potential as polymaths. These are people who can see the big picture from different perspectives and who can add that extra layer of innovative thinking and creativity to everything they do. And importantly the book also provides a framework for understanding how AI is likely to reshape the fundamental structure of the workforce, and how knowledge workers can strategically position themselves to enhance their value. This book provides an essential guide to developing new skillsets for knowledge workers in the AI era. Not only does it ensure that you don't fall behind, it will enable you to succeed and thrive"--